Effectiveness of Four Different Interventions Against Schistosoma haematobium in a Seasonal Transmission Setting of Côte d'Ivoire: A Cluster Randomized Trial. (14th September 2021) - Ouattara, Mamadou; Bassa, Fidèle K; Diakité, Nana R; Hattendorf, Jan; Coulibaly, Jean T; Yao, Patrick K; Tian-Bi, Yves-Nathan T; Konan, Cyrille K; Assaré, Rufin K; Koné, Naférima; Guindo-Coulibaly, Négnorogo; Utzinger, Jürg; et al.
Abstract: Background: Annual mass drug administration (MDA) using praziquantel is the cornerstone of schistosomiasis morbidity control but is not sufficient to interrupt transmission. We implemented a cluster-randomized trial to compare the effectiveness of 4 different intervention packages to interrupt transmission of Schistosoma haematobium in a seasonal transmission setting of Côte d'Ivoire. Methods: Sixty-four localities with a S. haematobium prevalence in school children aged 13–14 years above 4% were randomly assigned to 1 of 4 intervention arms over a 3-year period: (1) the current standard strategy consisting of annual MDA before peak of transmission, (2) annual MDA after peak of transmission, (3) biannual MDA, and (4) standard MDA combined with snail control. The primary outcome was prevalence and intensity of S. haematobium infection in children aged 9–12 years 1 year after the final intervention, using urine filtration performed by experienced microscopists. Results: By study end, we observed the lowest S. haematobium prevalence in the biannual MDA, compared to the standard treatment arm (0.6% vs 7.5%; odds ratio [OR] = 0.07, 95% confidence interval [CI] = .02 to .24). The prevalence in arms 2 and 4 was about 3.5%, which was not statistically significantly different from the standard strategy (both ORs 0.4, 95% CI = .1 to 1.8). New cases of infection were still observed in all arms at study end. Conclusions: Biannual MDA was the only regimen that outperformed the standard treatment. All strategies resulted in decreased prevalence of infection; however, none of them was able to interrupt transmission of S. haematobium within a 3-year period. Clinical Trials Registration: ISRCTN10926858. Abstract : Four different intervention packages substantially reduced the prevalence and intensity of Schistosoma haematobium infection in a seasonal transmission area. However, none achieved interruption of transmission. Snail control failed to boost the impact of preventive chemotherapy in this 3-year cluster-randomized trial.